The basic Kafka - Kafka (Pocket Books, 1979)
Contents: A fantastic collection with an invaluable selection of letters. If you have any interest in Kafka at all, and you're not well-versed, this is a great choice. There are some amazing pieces in here, as well as the collection of pathologies that constituted Kafka's unfortunate existence, and finally also some amazing... well what amounts to fragments.